Penerapan Metode SAW Dalam Sistem Keputusan Pemilihan Karyawan Terbaik Pada Butik Alratz Official - Novianti, Erin; Annisa Rahma, Wanda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This research aims to optimize the decision-making process in selecting the best employees at Alratz Official Boutique. The Simple Additive Weighting (SAW) method is applied in the decision system to analyze relevant criteria, such as skills, experience, and previous performance. This research integrates employee data, utilizing information technology to improve objectivity and efficiency in decision-making. The results of the study show that the application of the SAW method can increase the accuracy and speed of the employee selection process, assisting management in building a productive and high-performance team. The practical implications of this research can make a positive contribution to companies in improving productivity and service quality. Based on this, a company is inseparable from the role of humans to work in it. Quality to increase the productivity of a company's performance is one of the Human Resources (HR) factors. Therefore, a company needs to conduct an employee performance assessment for its success or unsuccess in performing tasks.